ANALYSIS OF STUDENTS' MATHEMATICAL REASONING ABILITIES ON TWO-VARIABLE LINEAR INEQUALITY SYSTEM MATERIAL - Nabila Nabila; Nicky Dwi Puspaningtyas (Universitas Muhammadiyah Metro, 2026)
This study aims to describe students' mathematical reasoning abilities in the subject of Two-Variable Linear Inequality Systems (SPtLDV). This study was conducted because many students still have difficulty understanding the concepts and steps for solving SPtLDV, especially in understanding the relationship between variables and drawing logical conclusions from a mathematical problem. These difficulties often arise when students have to interpret mathematical statements into inequalities and describe the solution area on a coordinate plane. This study used a qualitative descriptive method with 14 students from class XI of SMA Negeri 12 Bandar Lampung as subjects. Data were collected through mathematical reasoning ability tests and interviews to explore the students' thinking processes. The results show that students' mathematical reasoning abilities vary. High-ability students are able to meet all reasoning indicators, from making assumptions, performing mathematical manipulations, providing reasons for solutions, to drawing correct conclusions. Students with moderate abilities were still lacking in writing down the steps of manipulation systematically and tended to make small errors in calculations. Meanwhile, students with low abilities had difficulty understanding basic concepts and often made mistakes in manipulating the variables x and y, resulting in inaccurate solutions. Penelitian ini bertujuan untuk menggambarkan kemampuan penalaran matematis siswa dalam mata pelajaran Sistem Ketidaksetaraan Linear Dua Variabel (SPtLDV). Penelitian ini dilakukan karena banyak siswa masih mengalami kesulitan dalam memahami konsep dan langkah-langkah penyelesaian SPtLDV, terutama dalam memahami hubungan antara variabel dan menarik kesimpulan logis dari suatu masalah matematis. Kesulitan ini sering muncul ketika siswa harus menginterpretasikan pernyataan matematis menjadi ketidaksetaraan dan menggambarkan daerah penyelesaian pada bidang koordinat. Penelitian ini menggunakan metode deskriptif kualitatif dengan 14 siswa kelas XI SMA Negeri 12 Bandar Lampung sebagai subjek. Data dikumpulkan melalui tes kemampuan penalaran matematis dan wawancara untuk mengeksplorasi proses berpikir siswa. Hasil menunjukkan bahwa kemampuan penalaran matematis siswa bervariasi. Siswa dengan kemampuan tinggi mampu memenuhi semua indikator penalaran, mulai dari membuat asumsi, melakukan manipulasi matematis, memberikan alasan untuk solusi, hingga menarik kesimpulan yang benar. Siswa dengan kemampuan sedang masih kurang dalam mencatat langkah-langkah manipulasi secara sistematis dan cenderung membuat kesalahan kecil dalam perhitungan. Sementara itu, siswa dengan kemampuan rendah mengalami kesulitan memahami konsep dasar dan sering membuat kesalahan dalam memanipulasi variabel x dan y, yang mengakibatkan solusi yang tidak akurat.